Digital Marketing Competence and Continuance Intention: Marketing Performance Mediates; Top Management Support Moderates Relationship - Conny, Conny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Digital Marketing Competence on Marketing Performance and Continuance Intention, the influence of Marketing Performance on Continuance Intention, and the role of Marketing Performance as a mediation variable and Top Management Support as a moderation variable in salespeople who operate MSME stores on the Shopee platform. The research uses a quantitative approach with a survey method. Data was collected through a structured questionnaire that was distributed online to respondents who actively manage MSME stores on Shopee and were directly involved in digital marketing activities, such as content creation, promotion, and utilization of Shopee's marketing features. Variable measurements use a five-point Likert scale. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method which included the evaluation of measurement models and structural models, including mediation and moderation testing. The results of the study show that Digital Marketing Competence has a positive effect on Continuance Intention and has a strong influence on Marketing Performance. Marketing Performance has also been shown to have a positive effect on Continuance Intention and acts as a mediator in the relationship between Digital Marketing Competence and Continuance Intention. These findings indicate that digital marketing competencies not only increase the sustainability intention of using the platform directly, but also through improved marketing performance. In addition, Top Management Support does not have a direct effect on Continuance Intention, but is proven to strengthen the influence of Digital Marketing Competence on Continuance Intention.